Synthesis and spatial simulation of uniform binary codes - Білецький, А. Я.; Кучер, О. Г. (Proceedings of National Aviation University (archive), 2021)
The simulation algorithms of uniform binary codes formed by complete sequences of b-numbers of the nth order, Heming distance, in which between any adjacent code combinations, is an odd constant value that does not exceed the value of n-1.